Photosynthetic Response of Soybean and Cotton to Different Irrigation Regimes and Planting Geometries - Pinnamaneni, Srinivasa R.; Anapalli, Saseendran S.; Reddy, Krishna N. (Frontiers in Plant Science, 2022)
Abstract: In a two-year study (2018 and 2019), we examined gas-exchange and chlorophyll fluorescence parameters to better understand the regulatory and adaptive mechanisms of the photosynthetic components of cotton (Gossypium hirsutum L.) and soybean [Glycine max (L.) Merr.] grown under varied levels of irrigations and planting geometries, in a split-plot experiment. The main plots were three irrigation regimes; i) all furrows irrigation (AFI), ii) alternate or skipped furrow irrigation (SFI), and iii) no irrigation or rainfed (RF), and subplots were two planting patterns, single-row (SR) and twin-row (TR). The light response curves at vegetative and reproductive phases revealed lower photosynthesis rates in the RF crops than in AFI and SFI. Higher decrease was noticed in RF soybean for light compensation point (LCP) and light saturation point (LSP) than that of RF cotton. The decrease in maximum assimilation rate (Amax) was higher in soybean than cotton. A decrease of 12% and 17% in Amax was observed in RF soybean while the decrease is limited to 9% and 6% in RF cotton during the 2018 and 2019 seasons, respectively. Both stomatal conductance (gs) and transpiration (E) declined under RF. The moisture deficit stress resulted in enhanced operating quantum efficiency of PSII photochemistry (ΦPSII) which is probably due to increased photorespiration. The non-photochemical quenching (NPQ), a measure of thermal dissipation of absorbed light energy and quantum efficiency of dissipation by down-regulation (ΦNPQ) increased significantly in both crops up to 50% under RF condition. The photochemical quenching declined by 28% in soybean and 26% in cotton. It appears soybean preferentially uses non-photochemical energy dissipation while cotton uses elevated electron transport rate (ETR) under RF condition for light energy utilization. No significant differences among SR and TR systems were observed for LCP, LSP, AQE, Amax, gs, E, ETR and various chlorophyll fluorescence parameters. This study reveals differential regulation of photosynthesis apparatus in soybean and cotton, being C3 plants when exposed to moisture limited environments.